2018
DOI: 10.1016/j.bone.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Global deletion of tetraspanin CD82 attenuates bone growth and enhances bone marrow adipogenesis

Abstract: CD82 is a widely expressed member of the tetraspanin family of transmembrane proteins known to control cell signaling, adhesion, and migration. Tetraspanin CD82 is induced over 9-fold during osteoclast differentiation in vitro; however, its role in bone homeostasis is unknown. A globally deleted CD82 mouse model was used to assess the bone phenotype. Based on microCT and 4-point bending tests, CD82-deficient bones are smaller in diameter and weaker, but display no changes in bone density. Histomorphometry show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…At 6 months, bones are still remodeling, but by 9 months, they begin to regress. We saw this regression in both the WT and gKO mice, where we compared 6-month and 9-month bones by μCT ( Bergsma et al, 2018 ). Therefore, while bones are remodeling ( i.e.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…At 6 months, bones are still remodeling, but by 9 months, they begin to regress. We saw this regression in both the WT and gKO mice, where we compared 6-month and 9-month bones by μCT ( Bergsma et al, 2018 ). Therefore, while bones are remodeling ( i.e.…”
Section: Discussionmentioning
confidence: 91%
“…We previously observed that global loss of CD82 (gKO) results in decreased bone growth, reduced OB differentiation in vitro , and enhanced adipogenesis ( Bergsma et al, 2018 ). The microCT and histomorphometric data above indicate there are no overt bone defects in osteoblast-related functions in the cKO mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraspanins are implicated in a variety of membrane organization-related processes; therefore, future studies should investigate changes in sensitivity to membrane stressors in CD82-deficient cells (10,13). Although the cardiovascular system, eye, bone, and metabolism are impacted with deletion of CD82, mice are viable and have no physiological abnormalities (60)(61)(62)(63). Therefore, to demonstrate the relevance of our in vitro findings, we used an in vivo model of systemic candidiasis to show that mice lacking CD82 have enhanced susceptibility to Candida compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%